Greenhouse Gas Emissions and Obesity in Africa: A Disaggregated Panel Corrected Standard Error Model - Oyekale, Abayomi Samuel (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Obesity is a growing problem in Africa, promoting morbidity and contributing to mortality from non-communicable diseases. Although nutrition and genetic factors have been implicated in promoting obesity, the impact of environmental factors like carbon dioxide emissions is rarely emphasized in the literature. This paper contributes to the existing body of knowledge by providing empirical links between carbon dioxide emissions and obesity in Africa. The study used a longitudinal research design, and the data were from a panel of fifty-two African countries covering the 2000-2016 period. The data were sourced from the Food and Agriculture Organization (FAO) database and the World Bank’s World Development Indicators. Data analyses were implemented with a panel corrected standard error model due to the presence of contemporaneous correlation among some panels and the presence of cointegration. The results showed that obesity significantly increased, with p less than 0.05 across all regions, accompanied by increases in carbon dioxide emissions, per capita growth in gross domestic product (GDP), and the percentage of food imports. Political stability had mixed results on obesity, with positive impacts in West and Central Africa, and negative impacts in South Africa and in the combined results. It was concluded that addressing carbon dioxide emissions in Africa sends a positive signal towards reducing the incidence of obesity. A framework for African leaders to fully comply with the Paris Agreement is therefore crucial in mitigating the future impacts of GHG emissions on obesity and other associated health issues. Similarly, promotion of political stability and health-induced economic growth is vital for addressing the African obesity epidemic.